Textos autobiogràfics escrits per aprenents de català com a llengua addicional: de les necessitats formatives a la reflexió en l’ensenyament dels gèneres narratius - Bach, Carme (Caplletra. Revista Internacional de Filologia, 2022)
In this article we analyse autobiographical narrative texts written by university students studying Catalan as an Additional Language at a CEFR (2020) B1 level. The goal is to analyse the formative needs related to the writing of this genre in order to foster metadiscursive reflection in the classroom that will allow students to improve their written output. To this end, we analyzed a corpus of 39 autobiographies at both the macrotextual level (i.e., rhetorical moves) and the microtextual level (i.e., deictic elements which channel the narrative’s organization). Our results show that the problems that these texts present for students are related to awareness of the elements that define the genre (i.e., the sociocultural dimension) as well as the text’s narrative-temporal anchoring and the narrator’s deictic positioning (i.e., the pragmatic and textual dimensions). Thus, we propose a kind of competence-oriented teaching of genres in which the discursive and grammatical features that have a bearing on a text’s discursive coherence and cohesion are integrated at the same level.